Composite dietary antioxidant index is inversely and nonlinearly associated with cardiovascular disease, atherosclerotic cardiovascular disease, and cardiovascular mortality in people with dyslipidemia: evidence from NHANES 2001–2018 - Jiang, Yan; Shen, Yingying (Frontiers in Nutrition, 2025)
BackgroundDyslipidemia is a major risk factor for cardiovascular disease (CVD) and atherosclerotic CVD (ASCVD). The composite dietary antioxidant index (CDAI), an emerging measure of combined dietary antioxidant exposure, may provide insights into the relationship between diet and CVD/ASCVD outcomes. We aimed to explore the association between CDAI and the prevalence of CVD/ASCVD, as well as CVD mortality in individuals with dyslipidemia.MethodsCDAI was assessed by integrating dietary vitamins A, C, E, zinc, selenium, and carotenoids. Dyslipidemia was diagnosed according to widely established criteria. Data on CVD/ASCVD were obtained through self-reports, while CVD mortality was obtained through prospective matching participant records with the National Death Index database. Multivariate logistic regression analysis and Cox proportional hazards regression analysis were used to explore these associations and to calculate odds ratios [OR], hazard ratios [HR], and 95% confidence intervals [CI], respectively.ResultsA total of 23,126 participants with dyslipidemia from NHANES 2001–2018 were included. After adjusting for potential confounders, CDAI was inversely associated with the prevalence of both CVD and ASCVD in dyslipidemia populations (OR and 95% CI 0.979 (0.964, 0.995) and 0.977 (0.961, 0.993), respectively). Similar associations were observed between CDAI and specific types of CVD. CDAI was also inversely associated with CVD mortality in dyslipidemia participants (HR = 0.957, 95% CI = 0.939–0.976, p < 0.0001). Restricted cubic spline and threshold effects analyses indicated that CDAI was nonlinearly associated with CVD/ASCVD, with significant associations occurring only when CDAI≤0; however, the association of CDAI with CVD mortality was observed only when CDAI > −2. Furthermore, age, sex, and drinking were found to modify the association of CDAI with CVD/ASCVD, while body mass index influenced the relationship between CDAI and CVD mortality.ConclusionCDAI was inversely and nonlinearly associated with both CVD/ASCVD events and CVD mortality in dyslipidemic populations. These findings highlight the potential of antioxidant dietary patterns to alleviate the CVD burden in these populations and underscore the importance of personalized strategies.